The New Challenges and Situation of an Ethnic Minority within a Local Community in the Light of Social Changes - Kormányos Katona, Gyöngyi (Ethnographica et Folkloristica Carpathica, 2023)
Our memory is largely shaped by the way we look at the peoples currently living within the Carpathian Basin. Once a well-known tobacco-growing village in Historic Hungary, Torda (also known as Torontáltorda in Hungarian) is now a dispersed settlement with a Hungarian ethnic majority located in the Banat region of Vojvodina, Serbia. The shifting of national borders, the two World Wars, the events of the Yugoslav Wars and migratory movements have collectively changed and decimated the lives of Hungarians who had found themselves outside their motherland’s borders after the 1920s. In spite of the decline in population, the emigration of young people, and the everyday struggles resulting from hard living conditions, this village in the Central Banat district could attract further socio-ethnographic interest. In the micro-communities of rural settlements, education and religion play a key role in creating social value, maintaining Hungarian culture in the area and forming a national, local sense of identity within the community. Commemorative rituals, local traditions and national holidays often cross each others’ paths and blend together through education and religion, highlighting the reality and cultural values of the community, as well as the array of connections between community life and ethnic culture. This study discusses Torda’s present in the light of social change and the process of cultural mapping, touching on the importance of the local cultural association in the community’s life. This study also explores the events of the past few decades that have left a deep imprint on the micro-community’s life in a cultural, social and ethnic sense.